Digitalisasi dan Kualitas Layanan dalam Meningkatkan Kinerja Keuangan KSPPS: Studi Kasus BTM Pekalongan dengan Dana Pihak Ketiga sebagai Variabel Moderasi - Betty Pebriani; Usamah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study investigates the impact of service quality and digitalization on the profitability of KSPPS BTM Pekalongan, with Third-Party Funds (TPF) serving as a moderating variable. A quantitative approach was applied using a census method, involving 135 employees across 13 branch offices and 1 sub-branch. Data were collected through questionnaires and analyzed using moderated regression analysis (MRA). The results reveal that service quality has a positive and significant effect on profitability, while digitalization exerts a negative and significant influence. Additionally, Third-Party Funds negatively moderate the relationship between service quality and profitability, but positively moderate the relationship between digitalization and profitability. These findings underscore the importance of enhancing service quality and strategically implementing digitalization initiatives, alongside effective management of Third-Party Funds, to improve the financial performance of Islamic microfinance cooperatives.